Analytical study of the reality of scientific research and efforts to publish in Arabic in the United Arab Emirates (Khalifa University and the Emirates as a model) - Shaheen, Ranya Ahmed Rashid (Journal of Humanities & Social Sciences, 2022)
The study aimed to investigate the reality of scientific publishing in the United Arab Emirates at Khalifa University and the Emirates in particular, to show the extent of the state's interest in scientific publishing in its scientific institutions, and to highlight the Emirati effort to support scientific publishing in Arabic, and the state's financial and moral support for research and researchers during the period Between 2008 to the present time, and followed the descriptive analytical approach, to investigate the phenomenon, in order to determine the importance of scientific research in the state in general, and publishing in Arabic in particular, and it turned out that the state in 2008 started with small steps for scientific publishing, but it did not rise to the ranks of a wide global publication, However, by official decisions of the senior leadership, it has moved to the world, as I explained that for Khalifa University and the Emirates, Khalifa University has ranked 183 globally in publishing research and scientific progress in it.As for the efforts made to publish in Arabic, the state has sought to diversify its efforts between international conferences, refereed journals, electronic platforms, and research grants that support publishing in Arabic, and between national centers concerned with translating publications from Arabic into a second language.The study concluded that there should be an Arab database for international publishing houses that are interested in publishing in Arabic, as well as publishing houses that are interested in publishing in the UAE in particular, which facilitates the publication of researchers for their research, and the achievement of promotions and academic degrees.
Keywords: scientific publishing; globalization; support; standards; analysis; academic